2019
DOI: 10.1029/2018jb017289
|View full text |Cite
|
Sign up to set email alerts
|

Surface Motions and Continental Deformation in the Indian Plate and the India‐Eurasia Collision Zone

Abstract: The collision of the Indian plate with Eurasia has played a major role in controlling the dynamics of central Asia leading to the world's largest continental deformation zone. In order to study the deformation within the Indian plate as well as the India-Eurasia collision zone, we model the lithospheric stress field by calculating the two primary sources of stress, one arising due to topography and shallow lithospheric structure estimated by gravitational potential energy differences and the other arising from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 106 publications
(190 reference statements)
0
2
0
Order By: Relevance
“…Our research results further show that the contribution of gravitational potential energy to tectonic deformation is minimal in areas with large GPE values, such as the Qilian Mountains, while the influence of gravitational potential energy on tectonic deformation is indispensable in areas where the lateral gradient of the GPE changes drastically, such as the Qaidam Basin, the southern parts of the Alxa Block and the northern margin of the Qilian Mountains. The role of the GPE in the QFTB is different from that on the southern Tibetan Plateau, where the deviatoric stress generated by the GPE is strongly correlated with the GPS strain at the southern end of the main Himalayan Fault (Capitanio, 2020; Singh & Ghosh, 2019). The tectonic stress originating from the northward push of India into the southern Tibetan Plateau suppresses the influence of the GPE, and the two mechanisms act in opposite directions, but for the QFTB, the deviatoric stress generated by the GPE has a strong correlation with the GPS strain and focal stress in most areas, and these tensors present similar directions, suggesting that the GPE as a driving force affects the tectonic deformation of the QFTB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our research results further show that the contribution of gravitational potential energy to tectonic deformation is minimal in areas with large GPE values, such as the Qilian Mountains, while the influence of gravitational potential energy on tectonic deformation is indispensable in areas where the lateral gradient of the GPE changes drastically, such as the Qaidam Basin, the southern parts of the Alxa Block and the northern margin of the Qilian Mountains. The role of the GPE in the QFTB is different from that on the southern Tibetan Plateau, where the deviatoric stress generated by the GPE is strongly correlated with the GPS strain at the southern end of the main Himalayan Fault (Capitanio, 2020; Singh & Ghosh, 2019). The tectonic stress originating from the northward push of India into the southern Tibetan Plateau suppresses the influence of the GPE, and the two mechanisms act in opposite directions, but for the QFTB, the deviatoric stress generated by the GPE has a strong correlation with the GPS strain and focal stress in most areas, and these tensors present similar directions, suggesting that the GPE as a driving force affects the tectonic deformation of the QFTB.…”
Section: Discussionmentioning
confidence: 99%
“…Capitanio (2020) employed numerical modelling to constrain the boundary forces and lithospheric processes of Asian tectonics and supposed that the large‐scale coupling of the Indian margin and the southeastern Asian subduction could be significant contributing factors that gave rise to the contemporary deformation pattern of the Tibetan Plateau. Singh and Ghosh (2019) also showed that lithospheric buoyancy forces coupled with density‐driven mantle convection are largely able to explain the deformation of the Indian Plate and the northern collisional zone. Flesch et al (2001) showed that GPE differences have an important impact on the spatial variation in strain rates on the Tibetan Plateau and its periphery.…”
Section: Introductionmentioning
confidence: 99%